Osteosarcoma-Derived Small Extracellular Vesicles Enhance Tumor Metastasis and Suppress Osteoclastogenesis by miR-146a-5p - Araki, Yoshihiro; Aiba, Hisaki; Yoshida, Takeshi; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Miwa, Shinji; Igarashi, Kentaro; Nguyen, Tuan D.; Ishii, Kiyo-aki; Nojima, Takayuki; Takahashi, Satoru; et al. (Frontiers in Oncology, 2021)
Osteosarcoma is the most frequent type of primary bone tumor in children and adolescents, thus care for patients with malignant osteosarcoma is strongly required. The roles of small extracellular vesicles (SEVs) in enhancing metastases have been demonstrated in multiple tumors, but they are still poorly understood in osteosarcoma. Hence, this study investigated the effects of SEVs on progression and the tumor microenvironment in mice and patients. In an orthotopic implantation study, we found that osteosarcoma-derived SEVs had the potential to enhance metastases and angiogenesis. In addition, osteosarcoma-derived SEVs decreased the number of mature osteoclasts in vivo. In vitro osteoclastogenesis studies revealed that the inhibition of osteoclast maturation by osteosarcoma-derived SEVs was mediated by suppressing the NF-κB signal pathway. MicroRNA analysis of SEVs from different malignant human osteosarcomas revealed that miR-146a-5p was involved in the inhibition of osteoclastogenesis. In osteosarcoma patients, lower numbers of osteoclasts in biopsy specimens at the first visits were correlated with higher malignancy. These findings indicated that osteosarcoma-derived SEVs enhance distant metastasis of osteosarcomas by inhibiting osteoclast maturation, which may be a useful prognostic marker. This diagnostic method may enable to predict malignancy at early stage, and help to provide optimal care to patients with risk of high malignancy.